Z0 boson associated b-jet production in high-energy nuclear collisions*Supported by the Guangdong Major Project of Basic and Applied Basic Research (2020B0301030008), the Science and Technology Program of Guangzhou (2019050001), and the NSFC of China (11935007, 12035007, 12247127). S. Wang is supported by China Postdoctoral Science Foundation (2021M701279). (1st May 2023) - Wang 王, Sa 洒; Dai 代, Wei 巍; Zhang 张, Ben-Wei 本威; Wang 王, Enke 恩科
Abstract: The production of vector boson tagged heavy quark jets potentially provides new tools to probe the jet quenching effect. In this paper, we present the first theoretical study on the angular correlations ( ), transverse momentum imbalance ( ), and nuclear modification factor ( ) of boson tagged b -jets in heavy-ion collisions, which was performed using a Monte Carlo transport model. We find that the medium modification of the for + b -jet has a weaker dependence on than that for + jet, and the modification patterns are sensitive to the initial jet distribution. Additionally, with the high purity of the quark jet in + ( b -) jet production, we calculate the momentum imbalance and the nuclear modification factor of + b -jet in Pb+Pb collisions. We observe a smaller and larger of + b -jet in Pb+Pb collisions relative to those of + jet, which may be an indication of the mass effect of jet quenching and can be tested in future measurements.